Morphology, mineralogy and micromorphology of soils associated to summit depressions of the Northeastern Brazilian Coastal Plains - Silva,Elen Alvarenga (2012)
The scarcity of comprehensive characterizations of soils associated to gentle summit depressions of the Northeastern Brazilian Coastal Plains justifies this work, which had as objective to provide basic information for the more diverse agricultural and non-agricultural uses. For that, representative soils (Spodosols or similar soils) from these environments were selected in Alagoas, Sergipe and Bahia states. This approach included characterization of morphological, mineralogical and micromorphological properties of the soil profiles, employing standard procedures. The morphological characterization corroborated the effect of the podzolization process during the formation of these soils. The mineralogy of the clay fraction of these soils was basically composed of kaolinite and quartz, which, associated to the very sandy texture, helped in the understanding of the obtained data. The soil micromorphological study, besides confirming the field morphology, mainly in regard to the strong cementation, aggregated value to the work in terms of the secure identification of the clay illuviation process (non-identified in the field), in association with the dominant podzolization process.